Integrating the potential of ion mobility spectrometry-mass spectrometry in the separation and structural characterisation of lipid isomers - Camunas-Alberca, Sandra M.; Moran-Garrido, Maria; Sáiz, Jorge; Gil-de-la-Fuente, Alberto; Barbas, Coral; Gradillas, Ana (Frontiers in Molecular Biosciences, 2023)
It is increasingly evident that a more detailed molecular structure analysis of isomeric lipids is critical to better understand their roles in biological processes. The occurrence of isomeric interference complicates conventional tandem mass spectrometry (MS/MS)-based determination, necessitating the development of more specialised methodologies to separate lipid isomers. The present review examines and discusses recent lipidomic studies based on ion mobility spectrometry combined with mass spectrometry (IMS-MS). Selected examples of the separation and elucidation of structural and stereoisomers of lipids are described based on their ion mobility behaviour. These include fatty acyls, glycerolipids, glycerophospholipids, sphingolipids and sterol lipids. Recent approaches for specific applications to improve isomeric lipid structural information using direct infusion, coupling imaging or liquid chromatographic separation workflows prior to IMS-MS are also discussed, including: (i) strategies to improve ion mobility shifts; (ii) advanced tandem MS methods based on activation of lipid ions with electrons or photons, or gas-phase ion-molecule reactions; and (iii) the use of chemical derivatisation techniques for lipid characterisation.